Central East Slopes Wolf and Elk Study ... - Merrill, Evelyn (Borealis, 2025)
These are the telemetry data collected on both wolf and elk individuals as part of the Central East Slopes Wolf & Elk Study in Alberta, Canada. Elk telemetry data description: We captured adult, female elk during t using a net gun from a helicopter. Each animal was fitted with a Lotek GPS2200 collar (Lotek Wireless, Ontario, Canada) that collected locations every 2 h for up to 11 months. All procedures were approved Province of Alberta animal care permit #1432GP and Univ. of Alberta #300401-300601). Wolf telemetry data description: We captured wolves from 13 packs in 2002–2006 (pack sizes: 3–17 wolves) via helicopter net-gunning during winter months and with modified foot-hold traps during summer (University of Alberta Animal Care Protocols No. 391305, 353112, and 411601). We physically restrained wolves captured with helicopter net-gunning, whereas we either physically restrained or chemically immobilized wolves captured in traps. We fitted 13 wolves with Lotek (Lotek Engineering, Newmarket, ON, Canada) ... : Please notify Dr. Evelyn Merrill (emerrill@ualberta.ca) prior to using this data for your own research. Please cite this dataset if using in a publication. ...